2016
DOI: 10.5599/admet.4.4.322
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine and aurora kinase inhibitors diminish transport function of multidrug resistance-associated protein (MRP) 4 and breast cancer resistance protein (BCRP)

Abstract: Tyrosine and aurora kinases are important effectors in signal transduction pathways that are often involved in aberrant cancer cell growth. Tyrosine (TKI) and aurora (AKI) kinase inhibitors are anti-cancer MRP4: alisertib, danusertib, erlotinib, lapatinib, neratinib, nilotinib, pazopanib, sorafenib, and tozasertib. The potentially clinically relevant inhibition of BCRP was much more extensive and included alisertib, barasertib, danusertib, enzastaurin, erlotinib, gefitinib, imatinib, neratinib, nilotinib, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(54 reference statements)
1
0
0
Order By: Relevance
“…This study revealed for the first time that sulfasalazine can be successful in producing significant reductions in the protein expression levels of p-NFκB, BCR/ABL, p-STAT-3, p-Akt and VEGF and cause a significant increase in caspase-3 expression, which is in line with other studies [40][41][42][43][44][45], which could be the result of the inhibition of NFκB as one possible pathway for the decrease in VEGF because p-NFκB is considered to be a potent transcription factor that controls the expression of many downstream proteins, such as BCR/ABL, p-STAT-3, p-Akt and VEGF. In addition, crosstalk between the NFκB and p-STAT-3 pathways was found.…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed for the first time that sulfasalazine can be successful in producing significant reductions in the protein expression levels of p-NFκB, BCR/ABL, p-STAT-3, p-Akt and VEGF and cause a significant increase in caspase-3 expression, which is in line with other studies [40][41][42][43][44][45], which could be the result of the inhibition of NFκB as one possible pathway for the decrease in VEGF because p-NFκB is considered to be a potent transcription factor that controls the expression of many downstream proteins, such as BCR/ABL, p-STAT-3, p-Akt and VEGF. In addition, crosstalk between the NFκB and p-STAT-3 pathways was found.…”
Section: Discussionsupporting
confidence: 91%